2020
DOI: 10.1182/bloodadvances.2020001920
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Hematology 2020 guidelines for treating newly diagnosed acute myeloid leukemia in older adults

Abstract: Background: Older adults with acute myeloid leukemia (AML) represent a vulnerable population in whom disease-based and clinical risk factors, patient goals, prognosis, and practitioner- and patient-perceived treatment risks and benefits influence treatment recommendations. Objective: These evidence-based guidelines of the American Society of Hematology (ASH) are intended to support patients, clinicians, and other health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 155 publications
(294 reference statements)
3
106
0
1
Order By: Relevance
“…Current guidelines recommend intensive induction chemotherapy regimens in patients able to tolerate intensive treatment, optimally followed by allogeneic HCT [5,7,15], as this combination of treatment modalities represents the best potential for functional cure in AML. This approach also likely provides the greatest likelihood of achieving measurable residual disease (MRD) negativity, which has been shown in several studies to be prognostic of a reduced risk of relapse and improved survival in AML [16].…”
Section: Established Intensive Chemotherapy Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…Current guidelines recommend intensive induction chemotherapy regimens in patients able to tolerate intensive treatment, optimally followed by allogeneic HCT [5,7,15], as this combination of treatment modalities represents the best potential for functional cure in AML. This approach also likely provides the greatest likelihood of achieving measurable residual disease (MRD) negativity, which has been shown in several studies to be prognostic of a reduced risk of relapse and improved survival in AML [16].…”
Section: Established Intensive Chemotherapy Regimensmentioning
confidence: 99%
“…However, many of these studies were conducted several years ago and, more recently, a number of European trials have shown intensive induction chemotherapy can be associated with positive outcomes in this population (Table 1). Based on such studies, the American Society of Hematology recommends older patients with newly diagnosed AML who are eligible for intensive induction therapy should receive intensive therapy rather than less-intensive therapy or palliative care [15].…”
Section: Intensive Induction Chemotherapy In Older Patients and Patiementioning
confidence: 99%
See 1 more Smart Citation
“…For older patients not t enough to tolerate high intensity induction chemotherapy. the standard of care until recently was either low dose cytarabine or the use of hypomethylating agents such as azacitidine or decitabine [3]. Hypomethylating agents have been shown in clinical trials to improve median overall survival compared to conventional care regimens, however median overall survival still frequently remains less than 1 year, despite a reduction in chemotherapy related mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the benefits, the significant cost and discomfort associated with the frequent and long‐term hospitalizations and the treatment‐associated disability are difficult for patients and their relatives. With respect to these factors, it is important to select the patients who would benefit the most and to exclude the ones where the treatment would be ineffective and harmful 6,22–26 …”
Section: Introductionmentioning
confidence: 99%